Healthcare professionals’ attitudes and experiences of domestic violence - Dwivedi, Divya; Pandey, Uma; Lindow, Stephen W.; Narayan, Aditi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Domestic violence (DV) or intimate partner violence has been declared as public health epidemic by the WHO. Healthcare professionals (HCPs) have an important role in addressing the victims of DV or abuse and are the first to offer them care. Aim of study was to assess the attitude and professional experiences of HCPs concerning DV and their female patients. Methods: The study is conducted using pre-structured questionnaire and via google form sent to the study subjects through a WhatsApp link on their mobiles. The study population were comprises consultants, resident doctors and nurses. The study subjects’ response about receiving adequate training and their attitude whether enquiry about DV was considered an essential part of their job were the main outcomes. Results: A total of 392 responses were received. Overall, 50.3% of HCPs agreed that the incidence of DV has increased in the covid era and only 49.2% believe that enquiry about DV is an essential part of their job; 49.0% of HCPs agreed that they are comfortable while asking questions pertaining to DV. Only 17.4% of HCPs received adequate support during training period in regards to evaluating patients with DV. Conclusions: Training of all HCPs to identify and manage patients with DV is needed in order to deal efficiently with this public health problem. The attitude of HCPs towards DV needs to be addressed.